Actionable media :digital communication beyond the desktop - Tinnell, John (OUP, 2018)
In 1991, Mark Weiser and his team at Xerox PARC declared they were reinventing computers for the twenty-first century. The computer would become integrated into the fabric of everyday life; it would shift to the background rather than being itself an object of focus. The resulting rise of ubiquitous computing (smartphones, smartglasses, smart cities) have since thoroughly colonized our digital landscape. In Actionable Media, John Tinnell contends that there is an unsung rhetorical dimension to Weiser's legacy, which stretches far beyond recent iProducts. Taking up Weiser's motto, "Start from the arts and humanities," Tinnell develops a theoretical framework for understanding nascent initiatives--the Internet of things, wearable interfaces, augmented reality--in terms of their intellectual history, their relationship to earlier communication technologies, and their potential to become vibrant platforms for public culture and critical media production.